Production and Application of Monoclonal Antibodies Against Duck Plague Virus - Ravindra Dattatraya Padalkar (Department of Microbiology, College of Veterinary and Animal Sciences, 1999)
2. Monoclonal fltl~ibodies (Mabs) were raised against the vaccine strain r of OPY and three strains of OPY Viz, Vaccine (oPY - Y), IYRl (OPY -I) and AlIeppy strain (OPY -A) were used to raise polyclonal serum in the present investigation. DPY - Y was revived in 11 day old chicken embryo and the embryo death was recorded fout to five days PI with congestion all over the body . and spleen and necrotic foci in liver. The cytopathy in CEF cell culture observed was rounding ami clumping of the cells, syncytium formation and bridge fortnation with extensive vacuolation in the Cytoplasm. The detachment of the cells was observed at 120 h PI. DPY -I a virulent strain was inoculated in the ducklings, death was tecorded in all the inoculated birds with extensive hemorrhages on Serous membranes, muscles and visceral organs. Necrotic foci on liver,' enlargement and congestiol1 of liver and spleen, and white hecrotic foci in the gizzard were evident. The virus was further passaged ill DOE and